Appearances of Othering in The Story of “The Man in a White Coat” - Akar, Çağla (Edebi Elestiri Dergisi, 2022)
Oğuz Atay, build his works in context of stranger characters to the society they live in. The story “The Man in a White Coat” in the story book Waiting For Fear develops around an individual who is distant from the society to which he belongs, who exists as the “other” in the society due to the qualities he has or has not have. The subject, who is in a community, seems disconnected from the society because he can not communicate and exhibits an eccentric stance. The story centers conflict of society and individual by narrating tension between community and the subject. It is seen that the community tries to characterise and put the subject into some identities. However when the subject can not be included any social class, category and identify, it is seen that the community commence to be cruel and treats him unhuman. This behavior of the community become violent and they see the subject as a scape goat. It can be said that there is an increasing severity of othering violent. In this study, how othering takes place in the story as a sociological concept has examined and the appearances of othering in the story has revealed.
Keywords: Literary Studies; Oğuz Atay; “Beyaz Mantolu Adam”; othering; sociology; Oğuz Atay; “Beyaz Mantolu Adam”; ötekileştirme; sosyoloji; Edebi Çalışmalar; 5. Gender equality